Implementasi Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kompetensi Pedagogik Guru di SMP Negeri 9 Sarolangun - Efrina Juliyati; Samsu Samsu (JMiE (Journal of Management in Education), 2025)
This study aims to describe and analyze the implementation of academic supervision by the principal in improving teachers’ pedagogical competence at SMP Negeri 9 Sarolangun. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, classroom observations, and document analysis. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that academic supervision was conducted systematically through planning, implementation, evaluation, and follow-up stages. The planning stage was based on instructional needs and teachers’ readiness in preparing learning instruments. The implementation involved various supervision techniques, including checking instructional documents, classroom visits, observation, and teaching assessment. Evaluation was carried out objectively and dialogically, followed by follow-up actions such as coaching and recommendations for instructional improvement. Continuous academic supervision was found to contribute significantly to enhancing teachers’ pedagogical competence and improving the quality of learning. This study emphasizes the strategic role of principals as academic supervisors in supporting teachers’ professional development.